Toward improved survivorship: supportive care needs of esophageal cancer patients, a literature review. Issue 8 (12th October 2015) - Graham, L.; Wikman, A.
Summary: The growing prevalence of esophageal cancer survivors represent a population typified by an extensive treatment regime, significant postsurgical long‐term effects, and a dismal prognosis. Despite this, little is known of the supportive care needs of this patient group and the extent to which these are being met in practice. This review provides a synthesis of the research evidence to date; emphasizing opportunities for clinical application and setting a future agenda with research priorities. A literature search was performed using Medline/Embase, PsycINFO, and Web of Science. Search headings used included; [esophagus] or [esopohageal] or [upper gastrointestinal] or [upper GI] AND [cancer] or [carcinoma] or [squamous cell] AND [supportive care] or [survivorship] or [psychological] or [emotional] or [information] or [social] or [communication] or [spiritual] or [health‐related‐quality‐of‐life] or [HRQL] or [qualitative] or [patient narrative] or [clinical nurse specialist] or [CNS]. Related articles in English were reviewed, with additional articles harvested from reference sections. Esophageal cancer survivors report significant late‐term effects posttreatment, encompassing sustained impairment in most areas of health‐related quality of life. With a necessitated change in eating behavior, survivors find it particularly challenging to adjust to a new social identity and as a cancer population report high levels of psychological morbidity. Although the determinants of psychological morbidity are largely unknown, illness representations may be a key contributor. Several multidisciplinary supportive care interventions have been developed with promising results. The research summarized in this paper provides valuable insight into the psychosocial well‐being of the esophageal cancer survivor. However, knowledge gaps remain, alongside a dearth of applied examples in meeting supportive care need.